BS EN 2884. Aerospace series. Screws, pan head, offset cruciform recess, coarse tolerance normal shank, short thread, in titanium alloy, anodized, MoS2 lubricated. Classification: 1 100 MPa (at ambient temperature)/315 °C. (13th May 2020) - British Standards Institution,
No abstract available